Colour preference on Picture Therapy Cards in Children With ASD - Kusuma Wardani, Nuril; Fefiana Mustikasari, Bunga (KnE Social Sciences, 2023)
Children with Autism Spectrum Disorder (ASD) have difficulty understanding and concentrating. Several studies have explained that using visual therapy media, one of which is therapy cards, can help teachers and therapists maintain children’s concentration and motivation during learning. Previous research also states that ASD children have patterns of visual interest/preference for certain visual displays, in theory also explaining that visual displays affect children’s understanding and attention. One of the visual aspects on the therapy card is the colour used in the illustration on the card. This study aims to find out how colour combinations can affect children’s attention. We use a quantitative methodology with an experimental method by Chazin & Ledford. The results of the study found that autistic children prefer warm colour combinations, compared to illustrations with cool tone and monochrome combinations. Children also have better attention and motivation with cards with warm colour combinations in the illustrations. This research is expected to be useful input for teachers and therapists and can be used as a reference in making and developing visual media for children with autism. Keywords: autism, color, pictorial therapy cards